Aggregate Stability under Different Land Uses in Muntuk Village, Dlingo Subdistrict, Bantul Regency: Stabilitas Agregat pada Berbagai Penggunaan Lahan di Desa Muntuk, Kecamatan Dlingo, Kabupaten Bantul - Inayah, Heni; Arbiwati, Dyah (Jurnal Ilmu Tanah dan Air, 2025)
Stable soil aggregates improve soil structure and create a suitable medium for plant growth. Meanwhile. unstable aggregates break down easily under rainfall and accelerate erosion. This study aims to determine soil aggregate stability and the factors that control it under different land uses. The research used a survey approach. A land system map was produced by overlaying land use, slope, and soil type, resulting in 40 land system units. Sampling points were selected purposively based on land system units, accessibility, and land area. A total of 21 samples were collected. Aggregate stability was measured using wet and dry sieving. Observed parameters included field soil structure, texture, organic carbon, equivalent lime, specific gravity, bulk density, and clay content. Pearson correlation was used to identify the relationship between each parameter and aggregate stability. The results showed that aggregate stability ranged from 29.51-61.67 (unstable-slightly stable) in forest land, 52.02-84.90 (slightly stable-very stable) in mixed gardens, 34.22-64.25 (unstable-slightly stable) in rainfed rice fields, and 22.67-60.29 (unstable-slightly stable) in drylands. Soil organic matter and the dispersion ratio (DR) were the main factors influencing aggregate stability in Muntuk Village. Improving stability requires soil and water conservation practices that protect aggregates from breakdown by water or external disturbance. Agricultural land generally had lower stability, so proper management is needed. Recommended practices include returning crop residues, applying organic amendments, adopting minimum tillage, and implementing suitable cropping patterns.